James and the Giant Peach - Dahl, Roald; Illustrated by Blake, Quentin (London Puffin Books, 2013)
James Trotter is a lonely orphan boy living with his horrible guardian aunts until the day when something magical happens .....
Include Illustrations
Keywords: Fairy tales